Persuasive silence - Toru Suzuki (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
In the market where inattentive buyers can fail to notice some feasible choices, the key role of marketing is to make buyers aware of products. However, the effective marketing strategy is often subtle since marketing tactics can make buyers cautious. This paper provides a framework to analyze an effective marketing strategy to persuade an inattentive buyer in an adverse selection environment. We investigate how an attention-grabbing marketing can 'backfire' and when it can be effective.
Keywords: D03; D82; D83; L15; 330; signaling game; consideration set; counter signaling; limited attention; marketing; advertising